Mikroapartments in Deutschland – eine Analyse räumlicher Implikationen von Mikroapartmentanlagen - Hein, Simon (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Sustainable urban development requires the sustainable development of the housing sector. The Commission for Sustainable Building at the German Environment Agency, for example, recommends a reduction in per capita living space and developing sufficient floor plan designs. In this sense, microapartments are of particular relevance. Aside from climate change mitigation and resource efficiency, there are other challenges to sustainable urban spaces which have to be considered. To this end, this paper researches micro-apartments in the context of sustainable urban development planning. As a conceptual framework, the approach of a more spaceoriented housing research is tested. A possible revitalisation of urban niches is identified as the main potential of microapartment complexes. However, we find micro-apartments do not contribute to affordable housing for students, who are a main target group of micro-apartments. Further research on whether tenants of micro-apartments are increasingly outsourcing housing-related activities is needed, so that the socio-spatial implications of micro-apartments can be better understood.